Resveratrol attenuates oxidative stress during experimental periodontitis in rats exposed to cigarette smoke inhalation. (22nd October 2018) - Corrêa, Mônica Grazieli; Absy, Samir; Tenenbaum, Howard; Ribeiro, Fernanda Vieira; Cirano, Fabiano Ribeiro; Casati, Marcio Z.; Pimentel, Suzana Peres
Abstract : Objectives: This study aimed at investigating the effect of the systemic administration of resveratrol (RESV) on oxidative stress during experimental periodontitis in rats subjected to cigarette smoke inhalation. Material and Methods: Experimental periodontitis (EP) was induced in 26 male Wistar rats by the insertion of a ligature around one of the first mandibular and maxillary molars. The animals were assigned randomly to the following groups: cigarette smoke inhalation (CSI; 3 times/d, 8 minutes/d) + resveratrol (10 mg/Kg), that is, SMK + RESV (n = 13) and cigarette smoke inhalation + placebo, that is, SMK + PLAC (n = 13). The substances were administered daily for 30 days (19 days prior and 11 days following EP induction), and then, the animals were euthanized. The maxillary specimens were processed for morphometric analysis of bone loss, and the tissue surrounding the first maxillary molars was collected for mRNA quantification of Sirtuin 1 (SIRT1) by real‐time PCR. The gingival tissues surrounding the mandibular first molars were collected for quantification of superoxide dismutase 1 (SOD1) and nicotinamide adenine dinucleotide phosphatase oxidase (NADPH) using an ELISA assay. Results: Reduced bone loss was demonstrated in animals in the SMK + RESV group as compared to those in the SMK + PLAC ( P < 0.05) group on the basis of morphometric analysis. Resveratrol promoted higher levels of SIRT and SOD ( P < 0.05) as well as reduced levels of NADPH oxidase ( P < 0.05) were found in tissues derived from animals in the SMK + RESV group when compared to those in the SMK + PLAC group. Conclusion: Resveratrol is an efficient therapeutic agent that reduces exacerbation of bone loss found in animals with EP that were also exposed to smoke. The results suggest that its effects could be mediated, at least in part, by its antioxidant and anti‐inflammatory properties which attenuate the effects of oxidative stress on EP in the presence of cigarette smoke.